Polyneuropathy After Gastric By-pass Surgery - Hande Gazeteci Tekin; Sarenur Gökben; Sanem Yılmaz; Gül Serdaroğlu; Hasan Tekgül (Galenos Yayinevi, 2017)
Today rapidly increasing obesity causes significant morbidity and mortality. Gastric by-pass is frequently used for the treatment of morbid obesity, which cannot be controlled with diet and exercise. Although this treatment modality achieves rapid success, it also has several complications such as nutritional deficiency and its clinical results. We aimed to present a patient with polyneuropathy after having undergone gastric by-pass surgery for morbid obesity.